Epidemiology of intestinal parasitic infections in Babol City, Iran, during a seven years period: Epidemiology of intestinal parasitic - Ahmadnia, Zahra; Jafarian, Farzaneh; Ghorbani, Hossein; Firouzjahi, Alireza; Yahyazadeh-Jolodar, Arshia; Mohammadi-Abandansari, Rouzbeh; Darvishi-Ganji, Sodeh; Jafarian, Roja; Mashaee, Parham (Chronic Diseases Journal, 2025)
BACKGROUND: The north of Iran has a temperate and humid climate, leading to a higher prevalence of parasitic infections compared to other regions. This study aimed to determine the prevalence of intestinal parasitic infections in the northern part of Iran. METHODS: This qualitative, retrospective, descriptive-analytical, and cross-sectional study was conducted from March 2017 to the end of March 2024. Data from 6962 patients recorded in the Hospital Information System (HIS) of Ayatollah Rouhani Teaching Hospital in Babol City, Mazandaran Province, Iran, were analyzed. Direct microscopic examination and formalin-ether concentration techniques were used to diagnose intestinal parasites. Data analysis was performed using SPSS software, with frequency (percentage) calculation and chi-square test (P < 0.05). RESULTS: A total of 680 (9.76%) samples were infected with intestinal parasites. The prevalence was higher in women (54.30%) than in men (45.69%). Additionally, 55.80% of patients were from rural areas, while 44.19% were from urban areas. Entamoeba histolytica was the most common parasite, accounting for 32.05% of infections. The highest prevalence of parasitic infections was observed in the age group of 50-68 years (38%). CONCLUSION: The study confirmed the presence of various intestinal parasites in stool samples. Women had a higher infection rate than men, and most infected individuals lived in rural areas. Entamoeba histolytica was the most prevalent parasite.